A Systematic Review of Potential Opioid Prescribing Safety Indicators - Wael Y. Khawagi; Neetu Bansal; Nan Shang; Li-Chia Chen (Pharmacoepidemiology)
Background/Objectives: This systematic review aimed to identify a comprehensive list of potential opioid-related indicators from the published literature to assess prescribing safety in any setting. Methods: Studies that reported prescribing indicators from 1990 to 2019 were retrieved from a previously published systematic review. A subsequent search was conducted from seven electronic databases to identify additional studies from 2019 to June 2024. Potential opioid safety prescribing indicators were extracted from studies that reported prescribing indicators of non-injectable opioids prescribed to adults with concerns about the potential risk of harm. The retrieved indicators were split by each opioid, and duplicates were removed. The identified indicators were categorized by the type of problem, medication, patient condition/disease, and the risk of the indicators. Results: A total of 99 unique opioid-specific prescribing indicators were identified from 53 included articles. Overall, 42 (42%) opioid prescribing indicators focused on a specific class of opioids. Pethidine, tramadol, and fentanyl were the most frequently reported drugs (n = 22, 22%). The indicators account for six types of problems: medication inappropriate for the population (n = 20), omission (n = 8), inappropriate duration (n = 10), inadequate monitoring (n = 2), drug–disease interaction (n = 26), and drug–drug interaction (n = 33). Of all the indicators, older age (over 65) is the most common risk factor (n = 38, 39%). Central nervous system-related adverse effects are the risk of concern for the 28 (29%) indicators associated with drug–drug interactions. Furthermore, five of the six ’omission’ indicators are related to ’without using laxatives’. Conclusions: This review identified a comprehensive set of indicators for flagging patients at high risk of opioid-related harm, thereby supporting informed decision-making in optimizing opioid utilization. However, further research is essential to validate these indicators and evaluate their feasibility across diverse healthcare settings.